Influence of Dietary Sources of Melatonin on Sleep Quality: A Review. Issue 1 (19th December 2019) - Pereira, Nádia; Naufel, Maria Fernanda; Ribeiro, Eliane Beraldi; Tufik, Sergio; Hachul, Helena
Abstract: Sleep is an essential biological phenomenon, being a physiological and behavioral process necessary for quality of life. Melatonin is a circadian hormone produced at night by the pineal gland, regulated by the light/dark cycle, under the control of the suprachiasmatic nucleus. Melatonin is an indoleamine, synthesized from the essential amino acid tryptophan via serotonin. Melatonin is also found in plants, where it helps fight oxidative stress. To present a systematic review on the ability of food sources of melatonin to promote healthy sleep. A literature search was performed on the PubMed, Scopus, and ScienceDirect databases, including only randomized, placebo‐controlled trials published in English between 2005 and 2019. The methodological quality of the trials was assessed by the Jadad scale. Of the 25 eligible articles, eight met the inclusion criteria. They addressed the intake of milk or cherry juice in children, adults, and elderly subjects and evaluated sleep quality by questionnaires, sleep diary, actigraphy, or polysomnography. The analysis of the studies presented limitations, including lack of homogeneity of treatment dosage and duration. Nonetheless, the results indicated that the consumption of milk and sour cherries, sources of melatonin, may improve sleep quality in humans. These results pointed out to the potential suitability of food sources of melatonin as adjuvants in the prevention and treatment of sleep disorders. Further studies are necessary to better ascertain the aspects relevant to their use.